Analisis Nilai Tambah Dan Strategi Pemasaran Produk Olahan Brem Di Desa Bancong Kecamatan Wonoasri Kabupaten Madiun - Rekyani Puspitawati, Indah (JURNAL AGRI-TEK, 2017)
The agricultural processing industry can create added value. The added value obtained from the processing is the difference between the value of the commodities treated at a certain stage with the value of the corbanan used in the production process takes place. One of the usefulness of calculating value added is to measure the amount of service to the owners of production factor. With the superior product, Madiun people with knowledge, skill, tenacity and hard work develop small industry that process sticky rice into a processed product known as Brem.Dan one of brem production centers in Madiun District is Bancong Village Wonoasri Subdistrict. As a basis for calculating value added analysis is per kilogram of production. The price of raw materials used is the price at the consumer level. Other input prices are obtained from the purchase price in the month concerned, while the output price is obtained from the division between total sales output for a month with total production for a month for the same month. To see the influence of the environment, used internal and external factor analysis company. External factor analysis is used to look at threats from competitors and market opportunities. To see strategies that use environmental influences by using strengths, weaknesses, threats and opportunities. Business environment factors generally affect the strategy undertaken by the industry in marketing its products. This can be seen from the strategy implemented is the anticipation of the existing environmental factors. The strategy undertaken with respect to environmental influences is to maintain product quality. This industry has entered the stage of growth where the number of production in each year has increased despite very volatile.Keyword : Value Added, Marketing Strategy